Endodontic Retreatment in Underfilled Root Canal of Maxillary First Molar with Chronic Periapical Abscess: A Case Report - Nanik Zubaidah; Kun Ismiyatin; Cinitra Anindya; Nindhira Puspita Sari; Singgih Harseno; Ahmad Afif Dzulfikar; Dian Dwi Pratiwi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background:The failure of endodontic treatment commonly caused by imperfect obturation, periodontalperiradicularlesions, untreated root canals, and some other factors. The failure may trigger the occurrenceof secondary infections due to persistent. bacteria.One of the abnormalities that appear after endodontictreatment is a periapical abscess.Endodontic failure can be overcome by endodontic retreatment, apicalsurgery, or extraction. During an endodontic retreatment, endodontic instruments are used to remove theroot canal filling material and to repeat the steps of endodontic treatment to achieve the apical patency.Purpose: This case report presents management to overcome the failure of previous endodontic treatmentwith nonsurgical endodontic retreatment. Case: A 66 years old male patient came with a dull pain oftooth no 16 and uncomfortable when used for chewing since 2 months after endodontic treatment. Theepisodic swelling appeared since 3 months ago which then deflated.The objective examination showed apositive response to bite test and percussion test. Intraoral periapical radiograph confirmed an underfilledroot canal, and a periapical radiolucency with a diffuse border on palatal root. Case Management: Basedon the patient’s history taking, radiographic, and clinical examination,endodontic retreatment was doneand followed by porcelain fused to metal crown restoration. Conclusion: Endodontic retreatment is theappropriate treatmentoption to overcome the failure of the previous endodontic treatment that accompaniedwith a periapical lesion and to preserve its function in stomatognatic system.